No gender differences in mathematical problem-solving ability: A study with mathematics anxiety control - Dzulfikar, Ahmad; Turmudi; Herman, Tatang; Kusnandi (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
Equality, including gender, is an essential principle in school mathematics education and learning. Previous research findings, however, have yielded mixed results in terms of students’ mathematics proficiency, particularly mathematical problem-solving abilities. Furthermore, mathematics anxiety is frequently related to a decline in these abilities. As a result, the purpose of this study is to examine gender disparities in students’ mathematical problem-solving abilities while accounting for the influence of students’ mathematics anxiety. This study used a survey method with 96 students chosen by cluster sampling from a public junior high school in an urban area. This study included two instruments: a mathematical problem-solving abilities test and a mathematics anxiety scale. The findings of this study show that: (1) there is no significant difference in students’ mathematics anxiety based on gender, (2) gender has no significant effect on students’ mathematical problem-solving abilities after controlling for mathematics anxiety, and (3) mathematics anxiety has a significant effect on mathematical problem-solving abilities after controlling for gender. These findings highlight the need for strategies for reducing mathematics anxiety in children. Comprehensive assistance from the learning environment, including the responsibilities of parents, teachers, and friends, as well as a positive learning environment, is intended to assist students in overcoming mathematics anxiety. Thus, this study has significant implications for the development of inclusive and successful mathematics learning strategies.